Eurocentrism in the history of mathematics: the case of the Kerala School - DENNIS, F ALMEIDA and GEORGE JOSEPH, G (Race & Class 45(4): 45-59 2004, 2004)
To a typical historian of mathematics today, if there is one certainty, it is that Isaac Newton (1642-1727) and Gottfried Leibniz (1646-1716) were the first to `invent' a generalised system of infinitesimal calculus, an essential prelude to modern mathematics. However, at least two hundred years earlier, the astronomer-mathematicians of Kerala, notably Madhava of Sangamagrama and his disciples, had discovered elements of that calculus, the forerunners of modern techniques used in mathematical analysis. Given the existence of a corridor of communication between Kerala and Europe, especially from the sixteenth century onwards, and the crucial importance of calculus in the growth of modern mathematics, one would have expected that the possibility of the transmission of the Kerala mathematics westwards would be high on the agenda for historical investigation. That such an investigation has not yet been carried out may reflect, in our view, the strength and the pervasive nature of Eurocentrism in the history of science.